Analyzing the Influence of Cultural Factors, Social Factors, Personal Factors and Psychological Factors on Purchasing Decisions on Shopee: (Case Study on Gen Z Management Students) - Panggabean, Helena Louise; Noviaty, Evi; Hernaningsih, Fery; Heriyanto, Agustinus Yanuar Budhi (Universitas Mohammad Husni Thamrin, 2025)
The development of the digital market in Indonesia has made significant progress in recent years, especially in four main areas, namely financial technology (fintech), subscription services, e-commerce, and the Internet of Things (IoT). This study examines the influence of cultural, social, personal, and psychological factors on the purchasing decisions of Generation Z students on the Shopee e-commerce platform. Using a quantitative research approach, primary data was collected by distributing questionnaires to students of the management study program. The results of the t-test and F-test analysis showed that the four factors had a significant influence on purchasing decisions, both partially and simultaneously. Among the four factors, social influence emerged as the most dominant factor, with the highest t-value of 7.08 and a significance level of 0.000. These findings suggest that marketing strategies aimed at Gen Z consumers should prioritize social engagement, especially through influencers, online reviews, and social media platforms, and integrate cultural adaptation, personal relevance, and emotional approaches. The validity of the model is supported by the F value of 76.879 which exceeds the critical limit, and the Adjusted R Square value of 0.619, which indicates that 61.9% of the variation in purchasing decisions can be explained by the proposed variables. This finding emphasizes the importance of a comprehensive and multidimensional marketing approach that is in line with the values, lifestyles, and emotional factors of Gen Z consumers in the digital realm.